Personality of physical education teachers and adapted physical activity - Válková, Hana; Górny, Mirosław (Akademia Wychowania Fizycznego w Poznaniu)
The subject of personality of PE teachers has been investigated since the 1960s. The pioneering contributions to the area were made by Prof. Bohuslav Hodaň (Palacký University in Olomouc) and Prof. Bohumil Svoboda (Charles University in Prague).Nearly all Central European countries have dealt with similar problems related to physical education. The 1970s and 1980 s witnessed the regular organization of conferences around the subject of “Personality of PE teacher” as the basic platform for exchange of information and materials. The conferences were organized by Bohuslav Hodaň and the staff of the Department of Physical Education. They were organized every 2 years, and later every 3 years, from 1972 to 1981. The period of local projects in the late 1980s was marked with the development of the Czechoslovak government projects in cooperation with Poland and Hungary. The leading institution became the Faculty of Physical Education and Sports in Prague (Prof. B. Svoboda).The subject of “coaching” was included later. Local Palacký University projects focused on the education of PE specialists under the umbrella of elementary and/or special schools teachers. They had been the starting point for the training of Adapted Physical Activity professionals. The 1990s featured a focus on APA teachers, development of study programs, connecting theory with practice and assessment of graduates. A longitudinal project of assessment of PE teachers from the time of their university education through teaching practice to their retirement was a separate project which lasted 32 years (from 1974 to 2006).Research on PE graduates between 1998 and 2005 led by Prague and Olomouc sports faculties involved all departments of Physical Education in the Czech Republic. The aim of recent research focuses on study motivation, “successful – non-successful” graduates and curriculum development, especially within the APA and Recreology study programs.
Keywords: physical education undergraduates; physical education graduates; physical education teacher role; physical education professional competencies; adapted physical activity specialist